PREPARATION OF AN ORGANOSILICA-BASED MEMBRANE FROM TEOS-MTES AND ITS APPLICATION FOR DESALINATION OF WETLAND SALINE WATER - Lilis Septyaningrum; Rahmawati Rahmawati; Fitri Ria Mustalifah; Aulia Rahma; Dewi Puspita Sari; Muthia Elma (Universitas Lambung Mangkurat, 2020)
When hot season, South Kalimantan society which especially, in Muara Halyung village frequently go through clean water lacking. It becomes worst by water dirtied on wetland aquifer aftermath the seawater intrusion. Wetland water sources become saline and cannot be used for household needs. Organosilica membrane technology is one of methods can be used to remove salt contain in water. This study aims are to investigate the functionalization and organosilica membrane performance from TEOS-MTES which calcined on particularly temperature for wetland saline water desalination. Synthesis of organosilica sol was conducted by sol-gel method. Then the dried sol was calcined at 350°C and 600 °C, and characterized by FTIR (Fourier Transform InfraRed). Subsequently organosilica membrane was applicated for wetland saline water desalination via pervaporation. The result shows organosilica membrane performance was obtained the water flux 10,55 and 0,87 kg.m-2h-1 which calcined at 350 and 600 °C. The salt rejection in all membrane exhibits extremely high over 99%. It evinces the organosilica membrane from TEOS-MTES which calcined at 350 °C is great to applicated for wetland saline water desalination by both of water fluxes and salt rejection showed high.